7
$\begingroup$

Let's start by some well-known facts:

  • $H^1(\mathbb{R})$ is a Hilbert space, hence there holds the Riesz representation theorem, stating that any linear functional on it can be represented as $L = \langle \cdot , v\rangle$, where $v \in H^1(\mathbb{R})$, and $\langle \cdot, \cdot \rangle$ is the pairing in $H^1(\mathbb{R})$: $$ \langle u, v \rangle = \int_{\mathbb{R}} (u_x v_x + uv) d x. $$ Here, subscript indicates derivative.

  • Let $w \in L^2(\mathbb{R})$. Since the $H^1$-norm is stronger than the $L^2$-norm, the functional $v \mapsto L(v) := \int_{\mathbb{R}^2} w(x) v(x) d x$ is a continuous linear functional on $H^1(\mathbb{R})$.

My question is: is it possible to give the representative explicitly? In other words, find $z \in H^1(\mathbb{R})$ such that $L(v) = \langle v,z\rangle$.

I tried mimicking the proof of the Riesz theorem but it did not help. I am sure there is something really easy I don't see, but I seem to have some misconception here.

Any help would be appreciated.

$\endgroup$
  • 2
    $\begingroup$ This fact you can see it clearly if you are familiar with the characterization of the norm $H^1$ (or more generally $H^s$ with $s \in \mathbb{R}$ ) through the Fourier transform, and using the representation Riesz theorem. $\endgroup$ – user288972 Mar 12 '16 at 21:09
8
$\begingroup$

(i) $H^s(\mathbb{R}^n):=\lbrace u \in \mathcal{S}'(\mathbb{R}^n) : \Lambda^s u \in L^2(\mathbb{R}^n) \rbrace$ with $\omega_s(\xi):=(1+|\xi|^2)^{s/2}$, $\Lambda^s u := \mathcal{F}^{-1}(\omega_s \widehat{u})$ $\forall u \in \mathcal{S}'(\mathbb{R}^n)$, and by Plancherel theorem we have the norm

$$\left \| u \right \|_{H^s}= \left \| \Lambda^s u \right \|_{L^2}= \left\| \mathcal{F}(\Lambda^s u) \right\|_{L^2}=\left \| \omega_s \widehat{u} \right \|_{L^2}=\left( \int_{\mathbb{R}^n} |\widehat{u}(\xi)|^2 (1+|\xi|^2)^s d\xi \right)^{1/2}$$

Note that you can also define (ii) $H^s(\mathbb{R}^n):=\lbrace u \in L^2(\mathbb{R}^n) : \Lambda^s u \in L^2(\mathbb{R}^n) \rbrace$, the definition (i) is only a little more general. In particular, we have the scalar product

$$ (u,v)_{H^s}:=(\Lambda^s u, \Lambda^s v)_{L^2}= \int_{\mathbb{R}^n} \widehat{u}(\xi) (1+|\xi|^2)^s \overline{\widehat{v}(\xi)} d\xi.$$

Now $H^s(\mathbb{R}^n)$ and $H^{-s}(\mathbb{R}^n)$ are one of the dual isometric of the other. In other words for the space (iii) $H^s(\mathbb{R}^n)^* = \lbrace u \in H^s(\mathbb{R}^n)\longmapsto (u,v)_* : v \in H^s(\mathbb{R}^n) \rbrace$ we have $H^s(\mathbb{R}^n)^* \cong H^{-s}(\mathbb{R}^n)$, and likewise it is shown that $H^{-s}(\mathbb{R}^n)^* \cong H^{s}(\mathbb{R}^n)$. In particular, the application in (iii) are isometries, and $|(u,v)_*| \le \left \| u \right \|_{H^s} \left \| v \right \|_{H^{-s}}$.

Proof. let $v \in H^{-s}(\mathbb{R}^n)=\lbrace v \in \mathcal{S}'(\mathbb{R}^n) : \Lambda^{-s}v \in L^2(\mathbb{R}^n) \rbrace$ and $u \in H^s(\mathbb{R}^n)$. Consider the scalar product

$$ (u,v)_*:=(\Lambda^s u , \Lambda^{-s} v)_{L^2}=\int_{\mathbb{R}^n} \widehat{u}(\xi)(1+|\xi|^2)^{s/2} \overline{\widehat{v}}(\xi) (1+|\xi|^2)^{-s/2} d\xi$$

by Schwartz inequality $|(u,v)_*| \le \left \| u \right \|_{H^s} \left \| v \right \|_{H^{-s}}$. We show that $\forall v \in H^{-s}(\mathbb{R}^n)$, the maps $u \in H^{s}(\mathbb{R}^n) \longmapsto (u,v)_* \in \mathbb{C}$ is an element of the dual space $H^s(\mathbb{R}^n)^*$, infact if $T \in H^s(\mathbb{R}^n)^*$, by Riesz rapresentation therem: $$ \exists h \in H^s(\mathbb{R}^n): T(u)=(u,h)_{H^s} , \forall u \in H^s(\mathbb{R}^n) $$ and $\left \| T \right \|_*=\left \| h \right \|_{H^s}$. Define $v=\mathcal{F}^{-1}(\omega_{2s} \widehat{h})$, by Plancherel theorem we have $$ \left \| v \right \|_{H^{-s}} = \left \| \Lambda^{-s}v \right \|_{L^2} = \left \| \mathcal{F}\Lambda^{-s}v \right \|_{L^2} = \left \| \omega_{-s} \mathcal{F}v \right \|_{L^2} = \left \| \omega_{-s} \omega_{2s} \mathcal{F}h \right \|_{L^2} = \left \| \omega_s \mathcal{F}h \right \|_{L^2} < \infty $$ therefore $v \in H^{-s}(\mathbb{R}^n)$ with $h \in H^s(\mathbb{R}^n)$, and for the uniqueness $$ T(u)=(u,h)_{H^s} = \int_{\mathbb{R}^n} \widehat{u}(\xi) (1+|\xi|^2)^s \overline{\widehat{h}(\xi)} d\xi = (u,v)_{*} $$ and $H^s(\mathbb{R}^n)^* \cong H^{-s}(\mathbb{R}^n)$. In the end $$ \left \| T \right \|_{*} = \left \| h \right \|_{H^s} = \left \| \omega_s \mathcal{F}h \right \|_{L^2} =\left \| v \right \|_{H^{-s}}. $$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.